Clinical course of primary focal segmental glomerulosclerosis (FSGS) in Turkish children: a report from the Turkish Pediatric Nephrology FSGS Study Group - (:unkn) unknown (TURKISH J PEDIATRICS, 2010)
The clinical course of focal segmental glomerulosclerosis (FSGS) is heterogeneous in children. To evaluate the clinical course and the predictors of outcome in Turkish children with primary FSGS, a retrospective study was conducted by the Turkish Pediatric Nephrology Study Group in 14 pediatric nephrology centers. Two hundred twenty-two patients (92 boys, 130 girls, aged 1-16 years) with biopsy-proven primary FSGS were included. One hundred forty-eight patients were followed-up for a median of 51 months (range: 0.26-270). The clinical course was characterized by complete remission in 50 (33.8%), persistent proteinuria in 50 (33.8%) and progression to renal failure in 48 (32.4%) patients. Progression to end-stage renal disease (ESRD) was significantly higher in patients who did not attain remission. Complete remission, partial remission and progress to renal failure were recorded in 37%, 32% and 28%, respectively, of the patients (n=73) treated with prednisone combined cyclophosphamide/cyclosporine A. However, in patients (n=33) treated with pulse methyl prednisolone plus oral prednisone (up to 20 months) combined with cyclophosphamide, complete remission in 51.5% and partial remission in 27.3% of the patients were noted. Progression to renal failure was observed in 9.1% of this group of patients. Multivariate analysis showed that only plasma creatinine at presentation was an independent predictive value for outcome. Patients with serum creatinine level higher than 1.5 mg/dl had 6.6 times increased rate of progression to renal failure. Failure to achieve remission is a predictor of renal failure in children with primary FSGS. The use of immunosuppressive treatment in conjunction with prolonged steroid seems beneficial in primary FSGS in children.
Keywords: children; focal segmental glomerulosclerosis; treatment outcome; IDIOPATHIC NEPHROTIC SYNDROME; TERM FOLLOW-UP; INTRAVENOUS METHYLPREDNISOLONE; GLOMERULAR SCLEROSIS; ALKYLATING-AGENTS; KIDNEY-DISEASE; THERAPY; ADULTS; CYCLOPHOSPHAMIDE; PROGNOSIS